2013
DOI: 10.1007/s13353-013-0172-y
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and molecular analysis of genes Stpk-V2 and Stpk-V3 homologous to powdery mildew resistance gene Stpk-V in a Dasypyrum villosum accession and its derivatives

Abstract: Wheat-Dasypyrum villosum translocated chromosomes T6V#2S•6AL and T6V#4S•6DL are known to confer excellent resistance to wheat powdery mildew (PM). However, it is difficult to distinguish the two sources of PM resistance genes through multi-pathotype testing because to date no virulence for them has been found. To reveal the relationship between the PM resistance genes from the two translocations, the sequence of the Stpk-V gene, a key member of powdery mildew resistance locus Pm21, was used as a reference to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Previously, we isolated a Stpk-V homologous gene, Stpk-V3, in T6V#4S•6DL translocation line Pm97033, and found polymorphism between the two homologous genes (in both intron and regulatory (5´-UTR) regions). We further confirmed that the transcript levels of the two genes differed following challenge with the PM pathogen (Zhang et al 2012;Lin et al 2013). A recently developed anonymous marker, MBH1, can distinguish Pm21 and PmV loci on 6V#2S and 6V#4S unambiguous, respectively (Bie et al 2015).…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…Previously, we isolated a Stpk-V homologous gene, Stpk-V3, in T6V#4S•6DL translocation line Pm97033, and found polymorphism between the two homologous genes (in both intron and regulatory (5´-UTR) regions). We further confirmed that the transcript levels of the two genes differed following challenge with the PM pathogen (Zhang et al 2012;Lin et al 2013). A recently developed anonymous marker, MBH1, can distinguish Pm21 and PmV loci on 6V#2S and 6V#4S unambiguous, respectively (Bie et al 2015).…”
Section: Introductionsupporting
confidence: 72%
“…It is inferred that structural difference in chromatin could affect the pairing frequency of alien homologous chromosomes in wheat background. Although 6V#2S and 6V#4S were previously identified to confer differing responses to some diseases and to have polymorphisms detectable by molecular markers (Li et al 2002(Li et al , 2005aZhang et al 2012;Lin et al 2013;Bie et al 2015), their pairing behavior is totally unknown till now. In present study, we found in the PMCs of the F 1 hybrid progeny from a cross of translocation lines 6V#2S•6AL and 6V#4S•6DL that the two translocated chromosomes paired with their corresponding homologous wheat chromosomes (6A and 6D, respectively) via their long arms, forming two rod bivalents in most cases.…”
Section: Possible Reasons For the Low Pairing Frequency Of The Two Trmentioning
confidence: 99%
“…Although each of both T6V#2S·6AL and T6V#4S·6DL translocations contains a short arm of D. villosum chromosome 6V, broad polymorphisms have been revealed between 6V#2S and 6V#4S chromosomes, at both phenotypic and genotypic levels. Divergence between 6V#2S and 6V#4S at DNA sequential level has been revealed in previous studies (Bie, Zhao, Zhu, et al, ; Li, Chen, Shi, et al, ; Li et al, ; Lin et al, ; Liu, Li, Wang, Ye, & Lin, ; Zhang et al, ). Different response patterns to wheat streak mosaic virus, wheat cur l mite, and powdery mildew were also observed in various wheat‐ Haynaldia villosa 6V or 6VS lines (Chen, Shang, Steven, & Jpaul, ; Li et al, ).…”
Section: Introductionmentioning
confidence: 54%
“…The marker 6S‐19 was developed based on an expressed sequence tag (EST) located at the distal regions of chromosomes of wheat group 6 (Bie, Zhao, Jiang, et al, ), which can distinguish distal regions of D. villosum 6V#2S and 6V#4S. CINAU15m2, a proximal marker to Pm21 , developed based on the sequences of Stpk‐V alleles (Cao et al, ; Lin et al, ) in this study, can also distinguish the corresponding alleles on 6V#2S and 6V#4S. The primer pairs of MBH1 (F: GCCATTATAGTCAAGAGTGCACTAGCTGT; R: AGCTCCTCTCGTTCTCCAATGCT), 6S‐19 (F: CCAGTCGGAGAGGATCTCAA; R: TGGGCCTCTTGATCTTGACT) and CINAU15m2 (F: GTGCGCTGCATGTTTACTACTCAT; R: AAGTAATGCCGACAGTTTATCACAAT) were synthesized at Genebase Biotechnology Co.…”
Section: Methodsmentioning
confidence: 98%
“…The accumulation of Pm21 gene in a susceptible variety is a substantial aspect in both experimental breeding and commercial cultivation. Several studies were reported on the efforts to develop and exploit molecular markers to tag Pm21 (Qi et al, 1996;Liu et al, 1999;Cao et al, 2006;Song et al, 2009;Cao et al, 2011;He et al, 2013;Bie et al, 2015) and PmV (Lin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%